(3cja JQaY egGQGJc GdEOGQjI aj GdGJUGd (B/s - (3eGgQ, CMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3ebOeI aj GdGJUGd h GdLhGfH GdSdhcjI dg h GdGJUGd aj Xd KbGaGJ eNJdaI ceG Je GdJWQb Gdi GdGJUGd GdTahj HJfGhd GdGSJeGY h GdGJUGd ZjQ GdedahX h EOGQI GdGLJeGYGJ h GddLGf h eTGcd GdGLJeGYGJ h YdGLgG h GdebGHdGJ GdTNUjI h GdYQV GdTahj h CNjQG GdGJUGd GdcJGHj HeG aj egGQI GdbQGAI h GdcJGHI cegGQI ddGJUGd h GdNWGHGJ h GdeQGSdGJ h GdJbGQjQ (B.s
Keywords: (3GdGJUGds